(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Every building needs to apply building safety requirements in an effort to prevent and control fires by providing a Fire Extinguisher as fire protection. The availability of Fire Extinguisher needs to be supported by good knowledge from inhabitants. This study is aimed to determine the relationship between education, age, gender, work period and training to Fire Extinguisher knowledge. The research design is quantitative with a cross sectional approach. The research was conducted at Faletehan University Serang-Banten in April-July 2020 with the study population of all employees with a sample of 62 respondents taken by a simple random sampling method. Primary data collection using questionnaires with interview techniques. Data analysis was performed by univariate and bivariate using chi-square tests. The results of the analysis showed that 58,1% respondents were good knowledge about Fire Extinguisher, 88,7% respondents were highly educated, 69,4% respondents were aged ≤40 years, 61,3% respondents were female, 66,1% respondents had work period >5 years, and 69,4% respondents had never attended training. The results of the analysis showed that there is a relationship between education (p value=0,018) and training (p value=0,049) with Fire Extinguisher knowledge. Faletehan University needs to hold regular Fire extinguisher training that must be attended by all employees